The Correlation between Level of Mothers Knowledge in Bottle Feeding with Early Childhood Caries in Children Aged 3-5 Years Old - Dewi, Anggita .; Nugroho, Hari Wahyu (Nexus Kedokteran Klinik, 2016)
Introduction:Caries is a problem that happen in many children around the world. Bottle feeding is one of factors that can occur caries on childrenâs teeth. High level of mothers knowledge about bottle feeding is assumed can prevent their children from caries.This study aims to determine the correlation between level of mothers knowledge in bottle feeding with early childhood caries in children aged 3-5 years old. Methods:This research was a cross-sectional observational analytic study. The subjects of this study was mother of Islam Bakti XI Surakarta and Sri Juwita Hanum kindergarten student. The sample size was 113 mother which was taken by purposive sampling. This research was done by using Knowledge of Bottle (KBU) questionnare and examination of childrens teeth. Data was analyzed with spearman test by Statistical Product and Serve Solution (SPSS) version 21.0 for Windows. Results:This study showed that the correlation between level of mothers knowledge in bottle feeding with early childhood caries in children aged 3-5 years old were significant (r = 0,917, p = 0,000). Conclusions:This study concluded that there was correlation between level of mothers knowledge in bottle feeding with early childhood caries in children aged 3-5 years old. Keywords:level of motherâs knowledge, bottle feeding, early childhood cariesÂ